2020
DOI: 10.1108/mf-06-2020-0295
|View full text |Cite
|
Sign up to set email alerts
|

Expanding upon the weather: cloud cover and barometric pressure as determinants of attendance for NFL games

Abstract: PurposePurpose of the study is to further expand insights into how weather impacts attendance at sporting events. With the NFL having only eight home games a year per team, it is more of an event than other North American sports. We explore this in terms of how sensitive fans are to weather, by not only looking at traditional factors, but also other weather variables available through Accuweather. In addition, the authors explore team success, outcome uncertainty and other factors as determinants of demand.Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“… 8. As such, our sample does not include more recent studies that attempt to model the stadium attendance demand during a public health emergency, such as the recent COVID-19 pandemic (e.g., Reade & Singleton, 2020). Naturally, a small number of manuscripts exploring stadium attendance demand were published after we had finished our search process (e.g., Paul et al, 2020; Reade et al, 2020b; Wallrafen et al, 2020). …”
mentioning
confidence: 99%
“… 8. As such, our sample does not include more recent studies that attempt to model the stadium attendance demand during a public health emergency, such as the recent COVID-19 pandemic (e.g., Reade & Singleton, 2020). Naturally, a small number of manuscripts exploring stadium attendance demand were published after we had finished our search process (e.g., Paul et al, 2020; Reade et al, 2020b; Wallrafen et al, 2020). …”
mentioning
confidence: 99%
“…However, precipitation did not significantly affect KBL attendance as basketball is an indoor sport. This is particularly interesting given the previous studies (Anderson, 2016;Paul et al, 2020) that indicated that precipitation significantly reduced attendance even when events occurred indoors. As previously mentioned, fans may perceive basketball games as a unique experience that goes beyond the inconvenience and the negative emotions associated with rain exposure.…”
Section: Discussionmentioning
confidence: 68%
“…Previous studies have examined the impact of environmental barriers on the attendance of indoor professional sports (e.g. Thornes, 1977;Paul et al, 2020). Based on this research, air pollution and weather-related factors seem to deter fan attendance of indoor professional sports.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…We first consider studies in the former group. Paul et al (2021) find that not only precipitation but also cloud cover and barometric pressure negatively affect attendance in NFL games. Ehrlich et al (2021a) examine the marginal salary returns to offensive win production and defensive win production in Major League Baseball.…”
Section: Special Issue Articlesmentioning
confidence: 79%